2014
DOI: 10.1371/journal.pone.0092030
|View full text |Cite
|
Sign up to set email alerts
|

Park7 Expression Influences Myotube Size and Myosin Expression in Muscle

Abstract: Callipyge sheep exhibit postnatal muscle hypertrophy due to the up-regulation of DLK1 and/or RTL1. The up-regulation of PARK7 was identified in hypertrophied muscles by microarray analysis and further validated by quantitative PCR. The expression of PARK7 in hypertrophied muscle of callipyge lambs was confirmed to be up-regulated at the protein level. PARK7 was previously identified to positively regulate PI3K/AKT pathway by suppressing the phosphatase activity of PTEN in mouse fibroblasts. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
1
7
1
Order By: Relevance
“…PARK7 expression influences myotube size and myosin expression in skeletal muscle. Moreover, their expression is critical for Akt and mTOR activities . Upregulation of two different isoforms of myosin in the YT group may have contributed to the increase in PARK7, which was not observed in the OT group.…”
Section: Discussionmentioning
confidence: 99%
“…PARK7 expression influences myotube size and myosin expression in skeletal muscle. Moreover, their expression is critical for Akt and mTOR activities . Upregulation of two different isoforms of myosin in the YT group may have contributed to the increase in PARK7, which was not observed in the OT group.…”
Section: Discussionmentioning
confidence: 99%
“…PARK7 is an antioxidant protein that limits mitochondrial damage in response to oxidative stress (12) and it regulates skeletal muscle contractile protein synthesis and hypertrophy (149). Overexpression of PARK7 reduces mitochondrial dysfunction under oxidative stress (142) which shows a direct link between autophagy and mitochondrial function.…”
Section: Foxo Proteins and The Ubiquitin Proteasome System (Ups) In Mmentioning
confidence: 99%
“…Park7 has been associated with diverse biological processes including oxidative stress response, transcriptional regulation and cell survival [ 86 88 ]. Earlier in vitro study showed the significantly larger diameters and more total sarcomeric myosin expression in the Park7 (+/+) myotubes than in the Park7 (−/−) myotubes partially due to the altered activity of the PI3K/AKT pathway [ 27 ]. The up-regulation of PARK7 in callipyge lambs may lead to the enhanced activity and/or prolonged sustained activity of the PI3K/AKT pathway and in turn to increase the response of the downstream elements in the PI3K/AKT pathway to increase protein synthesis and muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…DLK1 mRNA was up-regulated in longissimus dorsi, gluteus medius and semimembranosus , the hypertrophied muscles in callipyge lambs but not up-regulated in supraspinatus , the non-hypertrophied muscle [ 13 , 15 , 24 , 25 ]. The DLK1 protein was expressed at high levels in the myofibers of callipyge longissimus dorsi and semimembranosus but was not detected in normal muscles [ 26 , 27 ] .…”
Section: Introductionmentioning
confidence: 99%